Simulation of the interaction between silica surface and acid or alkaline aqueous media - Kravchenko, A.A.; Demianenko, E.M.; Tsendra, O.M.; Lobanov, V.V.; Grebenyuk, A.G.; Terets, M.I. (Поверхность, 2015)
A quantum chemical analysis has been carried out of the equilibrium structure of hydrated HCl and HBr acid complexes and alkaline metal hydroxides on silica surface by means of density functional theory method with extended basis set 6-31++G(d,p) and exchange-correlation functional B3LYP. Deprotonation constants of silica surface hydroxyl group and of its cationic form have been calculated.